Effect of fluoride mouth rinses on various orthodontic archwire alloys tested by modified bending test: An in vitro study - Kamna Srivastava; Pavan Kumar Chandra; Nandini Kamat (Wolters Kluwer Medknow Publications, 2012)
Objective: Fluorides can cause corrosion and degradation in mechanical properties of commonly used archwires by forming hydrofluoric acid HF and causing disruption of protective titanium oxide layer. Hence, the aim of this study was to assess the change in load deflection characteristics of Ni-Ti, Cu Ni-Ti, S.S, and β-Ti wires on immersing in fluoride mouth rinses of two types- Phosflur and neutral NaF mouth rinse utilizing a modified bending test and comparing it to control. Materials and Methods: Round preformed wires were immersed in 10 ml of control and test solution (Phosflur and S-Flo mouth rinse) for 1.5 hours and incubated at 37°C. Modified bending test was carried out to evaluate load-deflection characteristics of different wires using Instron. Analysis of variance (ANOVA) was applied to determine if statistically significant difference exist among the mean load values obtained at various deflections in control and test solutions. Results: There was no statistically significant reduction in load deflection characteristics of Ni-Ti, copper Ni-Ti, β-Ti, and S.S wires on immersing in Phosflur mouth rinse and neutral sodium fluoride mouth rinses as compared to control at 2.5 and 1 mm of deflection in unloading phase. Conclusion: Phosflur and a neutral sodium fluoride mouth rinse did not affect the mechanical bending properties of Ni-Ti, copper Ni-Ti, B-Ti, and SS wires in in vitro conditions.